2015
DOI: 10.1146/annurev-nutr-071714-034355
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of mTOR Complexes in Lipid Metabolism

Abstract: The synthesis of lipids in response to food intake represents a key advantage that allows organisms to survive when energy availability is limited. In mammals, circulating levels of insulin and nutrients, which fluctuate between fasting and feeding, dictate whether lipids are synthesized or catabolized by tissues. The mechanistic target of rapamycin (mTOR), a kinase that is activated by anabolic signals, plays fundamental roles in regulating lipid biosynthesis and metabolism in response to nutrition. The mTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
207
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(213 citation statements)
references
References 156 publications
(198 reference statements)
4
207
0
2
Order By: Relevance
“…mTOR pathway, was also assessed, but again, no statistical difference was detected between groups. GLUT1, which increases glucose uptake into cells (28), was shown to be upregulated in the experimental group. Changes in protein fold were quantified and revealed that the greatest difference between the groups was in mTOR, p-mTOR, p4EBP1, pS6 and GLUT1 levels, all of which were increased in the knockout mice.…”
Section: Downstream Targets Of Mtor Were Upregulated Inmentioning
confidence: 88%
See 1 more Smart Citation
“…mTOR pathway, was also assessed, but again, no statistical difference was detected between groups. GLUT1, which increases glucose uptake into cells (28), was shown to be upregulated in the experimental group. Changes in protein fold were quantified and revealed that the greatest difference between the groups was in mTOR, p-mTOR, p4EBP1, pS6 and GLUT1 levels, all of which were increased in the knockout mice.…”
Section: Downstream Targets Of Mtor Were Upregulated Inmentioning
confidence: 88%
“…While the former two effectors -pS6 and p4EBP1 -stimulate protein synthesis, the lattermost -GLUT1 -regulates glucose transport (28). Specifically, GLUT1 increases glucose uptake into cells, and its upregulation may be indicative of increased metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the other nutrient intake changes (except dietary carbohydrate or protein intake), we employed a controlled-feeding method for in vivo studies. As our recent work demonstrated that hepatic lipogenesis requires the activation of mechanistic target of rapamycin complex 1 (mTORC1) in rainbow trout (14,15,42) as in mammals (9,41,63), and elevated amino acid levels enhanced hepatic fatty acid biosynthetic gene expression through an mTORC1-dependent manner (15), we also investigated the potential involvement of mTORC1 signaling pathway in the present study. Acute administration of rapamycin, a pharmacological inhibitor of mTOR, was employed to achieve an inhibition of mTORC1 and its downstream effectors, including p70 ribosomal S6 kinase 1 (S6K1), S6, and eukaryotic initiation factor 4E (eIF4E)-binding protein 1 (4E-BP1) (14 -16, 42, 74).…”
mentioning
confidence: 99%
“…Activated mTOR stimulates angiogenesis, which increases the number of blood vessels through which nutrients can reach the cell. It also increases the production of nutrient transporter proteins that enhance the cell’s ability to import essential nutrients, and stimulates glycolysis and lipid metabolism [130]. Once extracellular and intracellular factors activate mTOR, it induces lipid and nucleotide synthesis and, in turn, promotes cell proliferation and survival.…”
Section: Local Molecular Mechanisms In Malnutrition and Cu Growthmentioning
confidence: 99%